The Beneficial Effects of Exercise and Date Palm Pollen Supplement on Liver Histopathology in the Cadmium Chloride Toxicity Model - Delshad, Amir; Azimzadeh, Maryam; Salimi, Fereshteh; Eslami Farsani, Mohsen; Ababzadeh, Shima; Seyedebrahimi, Reihaneh (Shahroud Journal of Medical Sciences, 2026)
Background: Cadmium (Cd) is a highly toxic heavy metal that poses a significant health risk in vital organs such the liver. This study investigates the protective effects of aerobic exercise and hydroalcoholic extract of Date Palm Pollen (DPP) in rat Cd toxicity model.Methods: Thirty-six male Wistar rats (230-250 g) divided to six experimental groups (n=6): control, exercise, Cd, Cd-exercise, Cd- exercise-200 DPP, and Cd-Exercise-400 DPP. Each group received a daily dose of 3mg/kg of Cd chloride via gavage. Then, DPP extract was administered intraperitoneally at doses of 200 and 400 mg/kg/day. The aerobic exercise protocol was involved the rats running on a treadmill at a speed of 27 meters/min, with an additional minute added to the training duration each day. The enzyme levels (AST, ALT, GGT) were measured and the histopathological analysis of liver tissue were performed after 5 weeks.Results: Results demonstrated that treatment groups have the significant decrease of GGT and ALT serum levels compared with Cd group (GGT; P-value<0.001, ALT; P-value<0.05). However, there were no significant difference in AST serum level between different groups. Besides, the histopathological findings revealed the number of necrotic areas, sinusoids congestion, and inflammation in Cd group while these alternations were decreased in treatment groups compared with injured group.Conclusions: The findings demonstrating that the combination of aerobic exercise and DPP extract effectively reduce inflammation and cellular damage in liver tissue. So, DPP extract with 200 mg/kg concentration along with regular exercise has hepatoprotective potential effect.